2021
DOI: 10.30773/pi.2020.0337
|View full text |Cite
|
Sign up to set email alerts
|

Validating the Autism Diagnostic Interview-Revised in the Korean Population

Abstract: Objective This study aimed to examine the validity of the Korean version of the Autism Diagnostic Interview-Revised (K-ADI-R) and determine its efficacy in identifying individuals with autism spectrum disorder (ASD).Methods Data were pooled from several past and ongoing studies as well as clinical records acquired at Seoul National University Bundang Hospital from 2008 to 2017. The K-ADI-R were administered and scored by trained research reliable examiners. Measurements to investigate the validity of the K-ADI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 41 publications
(70 reference statements)
0
10
0
Order By: Relevance
“…Another study by the author has also demonstrated the high validity of the Korean ADI-R in ASD detection in comparison with the OD group. 42 Furthermore, the significant difference in SRS mean scores was maintained in the subgroup analysis of children aged below 30 months. The result supports that the SRS preschool form may sustain its diagnostic efficacy in Korean children population even below its original indicated age group, and can thus aid in prescreening procedures for children below 30 months.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Another study by the author has also demonstrated the high validity of the Korean ADI-R in ASD detection in comparison with the OD group. 42 Furthermore, the significant difference in SRS mean scores was maintained in the subgroup analysis of children aged below 30 months. The result supports that the SRS preschool form may sustain its diagnostic efficacy in Korean children population even below its original indicated age group, and can thus aid in prescreening procedures for children below 30 months.…”
Section: Discussionmentioning
confidence: 83%
“…This may suggest that SRS may be employed not only as a screening instrument to differentiate ASD and non-ASD, but may also aid in the in-depth screening and diagnosis of ASD, supporting the endeavor to detect and differentiate ASD from other development disorders. Another study by the author has also demonstrated the high validity of the Korean ADI-R in ASD detection in comparison with the OD group [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Speci cally, some parents may have di culties reporting their child's social interaction abilities because young children's social dynamics tend to be passive or exclusively with adults [57]. Caregivers' beliefs, characteristics, acceptance, and awareness of autism may in uence how they interpret their child's behaviors [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…11 The ADI-R can be administered for children and adults, as long as their mental age is above 18 months. The ADI-R has been translated to 19 languages 12 and used in non-English countries such as Brazil, 13 Greek, 14 Japan, 15 Korea, 16 Taiwan 17 and so on. The case numbers of the validation studies varied from study to study.…”
Section: Introductionmentioning
confidence: 99%